SISTEM INFORMASI PEMASARAN USAHA KECIL MENENGAH (Studi Kasus: Sujiane Bidang Snack Dan Food Di Kota Medan) - Permana Pane, Arya Duta; Annisa, Moza; Aulia, Windi; Harnita, Rizki; Suhairi, Suhairi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the marketing information system in small and medium enterprises. The type of research used is descriptive research, namely research that aims to find a description of the characteristics of the population being studied. This type of research uses qualitative research. Data Collection Techniques Primary data and secondary data were obtained by conducting interviews and surveys in the field. Population and Sample The population in this study includes all Snack and Food SMEs in Medan City. The sample was taken based on the characteristics of the company, namely companies that absorb a lot of workers. Data Analysis Method Data analysis method using qualitative data. The results of this study Profile of SMEs in Sujiane which are engaged in Snack and food in Medan City as follows SME products already have characteristics, only there is no variation, this is because SMEs are mostly engaged in the culinary field. Constraints in the application of Marketing Information Systems there are no data and documentation integrated from the UMK. The existence of a blog about the profile of SMEs in Sujiane which is engaged in Snack and food in Medan City.